2016
DOI: 10.1002/adv.21691
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Isotactic Polypropylene (iPP)/Poly(lactic acid) (PLA) and iPP/PLA/Nano Calcium Carbonates Using Phanerochaete chrysosporium

Abstract: Phanerochaete chrysosporium species was used to study the degradation of polymeric composites of (a) isotactic polypropylene (iPP) and (PLA) (iPP/PLA), and (b) iPP/PLA filled with calcium carbonate nanoparticles (nCaCO 3 ). PLA was synthesized using L-lactic acid under the controlled ultrasound cavitation technique, dried and used for composite preparation. Meanwhile, the synthesis and subsequent surface modification of nCaCO 3 was done using the ultrasound cavitation technique. Owing to ultrasound cavitation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…In addition, from the turbidity of the solution, it was observed that there was fungi growth (as seen in Figure 18a,b). In the Shimpi et al [135] study, all the compositions exhibited fungal growth between 7 to 28 days. Maximum turbidity was noticed at the 28th day because of the stationary phase and lyses fungal biomass.…”
Section: Pla Biodegradationmentioning
confidence: 89%
See 3 more Smart Citations
“…In addition, from the turbidity of the solution, it was observed that there was fungi growth (as seen in Figure 18a,b). In the Shimpi et al [135] study, all the compositions exhibited fungal growth between 7 to 28 days. Maximum turbidity was noticed at the 28th day because of the stationary phase and lyses fungal biomass.…”
Section: Pla Biodegradationmentioning
confidence: 89%
“…The study concluded that both iPP/PLA composites and iPP/PLA/nCaCO 3 nanocomposites support fungal growth of P. chrysoporium, which leads to degradation and is revealed through the production of biomass, excretion of extracellular protein, and reshaping of the matrix structure with a proportion transformation in degradation. In the Shimpi et al [135] study, all the compositions exhibited fungal growth betw 7 to 28 days. Maximum turbidity was noticed at the 28th day because of the station phase and lyses fungal biomass.…”
Section: Pla Biodegradationmentioning
confidence: 89%
See 2 more Smart Citations
“…These microorganisms usually contain enzymes with depolymerizing capacity, thereby being able to actively shorten polymerized chains and degrade polymeric materials. Notable examples include degraders of PE, such as bacterial species from the genera Lysinibacillus and Brevibacillus and the fungus Penicillium simplicissimum ( Yamada-Onodera et al 2001 ; Hadad et al 2005 ; Jeon et al 2021 ), PET, such as the bacterium Thermobifida fusca and species from the genera Acidovorax and Ideonella (Roth et al 2014 ; Yoshida et al 2016 ; Jachimowicz et al 2022 ) and PP, such as bacteria from the genera Lysinibacillus , Serratia and Enterobacter and the fungus Phanerochaete chrysoporium (Shimpi et al 2018 ; Jeon et al 2021 ; Wróbel et al 2023 ), all of which are widely used and prevalent as environmental pollutants (Table 1 ). Regarding bioplastics, despite their limited presence in natural environments, extensive research has identified microorganisms capable of biodegrading them.…”
Section: Microbial Biofilms On Microplasticsmentioning
confidence: 99%